Formulation of Impatiens balsamina L. Leaf Extract Nanoemulsion and Its Activity Against Foodborne Pathogen Salmonella Spp. - Cahyaning Rini Utami; Alfiyah Nur Rohmah Ida (University of Sultan Ageng Tirtayasa, 2026)
Growing demand for safer preservatives has increased interest in plant-derived antimicrobials, yet many bioactives show poor compatibility and instability in aqueous systems. This study formulated and characterized Impatiens balsamina L. leaf-extract nanoemulsions and assessed anti-Salmonella activity using disc diffusion and broth microdilution. The ethanolic extract (maceration) showed a positive Mg–HCl reaction and contained 60.19 ± 0.015 mg GAE/g total phenolics and 28.25 ± 0.12 mg QE/g total flavonoids. Nanoemulsions were prepared with Tween 80:propylene glycol ratios F1 (5:1), F2 (6:1), F3 (7:1), and F4 (1:0), then evaluated for pH, viscosity, droplet size (PSA), PDI, zeta potential, TEM morphology, and homogeneity during 0–21 days. All formulations were acidic (pH 4.13–4.23) with no significant differences. Droplet size decreased from 176.06 nm (F1) to 30.56 ± 0.6 nm (F4) with a low PDI (0.226 ± 0.2), higher viscosity (32.0 ± 0.2 cP), and zeta potential of −19.98 ± 0.04 mV; only F4 remained homogeneous through 21 days and showed fine, near-monodisperse droplets in TEM, yielding the highest De Garmo index (0.89). F4 produced an 11.65 ± 0.24 mm inhibition zone versus crude extract (10.26 ± 0.19 mm) and blank nanoemulsion (2.34 ± 0.17 mm). MIC/MBC confirmed concentration-dependent activity for F4 (6.60 ± 0.03/13.75 ± 0.02 mg/mL) compared with the crude extract (7.50 ± 0.02/14.23 ± 0.01 mg/mL). Overall, formulation optimization improved dispersion robustness and modestly enhanced anti-Salmonella performance under standardized conditions; validation in representative food matrices remains necessary.